Strategi Guru PAI Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa YPI Darul Abror di Masa Pandemi - Paisal, Pahmi; Irfani, Fahmi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
The impact of Covid-19 learning is that students experience boredom and learning difficulties,resulting in a decrease in the student learning process during learning activities. Therefore, PAIteachers must strive to redevelop teacher strategies to improve students' reading ability of the Qur'an at YPI Darul Abror school during the pandemic. The purpose of this study is to analyze the effect of PAI teacher strategies on the ability to read the Qur'an. The method in this study uses a quantitative research method that has an inductive, objective and scientific nature where the data obtained is in the form of numbers (scores/values) or statements that are assessed, and analyzed using statistical analysis. The results of this study are that there is an influence between the strategy of the PAI teacher and the ability to read the Qur'an of YPI Darul Abror students. The teacher's strategy is made to achieve learning objectives, can encourage student activities during learning, can develop individual students during learning, can develop psychomotor aspects and aspects of all aspects of student life in an integrated manner to improve the ability to read the Qur'an during a pandemic.